2009
DOI: 10.1038/ijo.2009.134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of waist circumference cutoffs for abdominal obesity in the Chinese population: a 7.8-year follow-up study in the Shanghai urban area

Abstract: Aim: To identify the appropriate visceral adipose tissue (VAT) cutoff values for the diagnosis of abdominal obesity in predicting diabetes and the corresponding waist circumference in the Chinese population. Methods: At baseline, 381 volunteers aged 35-75 years were enrolled without diabetes from the Shanghai urban area. Anthropometry and VAT area determined by magnetic resonance imaging were measured. During the average 7.8 years of follow-up, glucose tolerance was monitored. Receiver operating characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Women in our group had higher TBF, as shown by greater thickness of subcutaneous fat and higher visceral fat mass, when compared to males. Higher visceral fat tissues in females with DM has also been reported by Ye et al [4]. Higher VFA in women with T1D could be related to more frequent oscillations in glycaemia during the menstrual cycle.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Women in our group had higher TBF, as shown by greater thickness of subcutaneous fat and higher visceral fat mass, when compared to males. Higher visceral fat tissues in females with DM has also been reported by Ye et al [4]. Higher VFA in women with T1D could be related to more frequent oscillations in glycaemia during the menstrual cycle.…”
Section: Discussionsupporting
confidence: 68%
“…In non-obese women with T1D, the higher central depots of fats are the main determinant of MS, while peripheral fat distribution and total fat percentage show no correlation with MS [1]. Men without diabetes have higher visceral adiposity compared to women without diabetes, while men with diabetes have lower visceral adiposity compared to women with diabetes [4]. Results of The Diabetes Control and Complications Trial Research Group (DCCT) showed that intensive glycaemic control reduces the incidence and progression of microvascular complications in T1D [5], but also leads to body weight (BW) increase [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified thresholds of VAT that are related to elevated cardiometabolic risk factors and metabolic syndrome (MetS) in white men and women (5)(6)(7)(8)(9). Limited studies have also identified optimal thresholds of VAT in other ethnic groups such as Indians (10), Chinese (11), Koreans (12,13), Japanese (14,15), and Japanese Americans (16).…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index (BMI) was calculated as measured weight in kilograms divided by measured height in meters squared and categorized using the World Health Organization (WHO) classifications [6]: overweight (≥25 kg/m 2 ) or not (<25 kg/m 2 ). Waist circumference (WC) measurements were used as a measure of central adiposity, and classified into two categories: obesity (≥90 cm) or not (<90 cm)) [7].…”
Section: Methodsmentioning
confidence: 99%